MENUMBUHKAN BISNIS ONLINE DAN FINANCIAL TECHNOLOGY (FINTECH) UNTUK PENGELOLAAN KEUANGAN KELUARGA - Ayu, Maristiana; Azriya, Niar (JURNAL ABDIMAS DOSMA (JAD), 2023)
Through extension activities. Has encouraged the growth of online business and the financial technologi (fintech) to giving any education about digital business and the financial technology in their knowledge for managing the family money. The large number of the communities hit by the case of false transactions and loan fraud online shopping online and this is because one of them is their level of understanding about knowledge online business and the financial technology are not enough for the community especially in villages where it. The expansion of the business online and fintech emerging economies in the financial landscape of Indonesia was very it is important to note by all groups in the community especially in the village area including west Sukadanaham urban village tanjung coral Bandar Lampung. Activities devotion was attended 23 people sukadanaham urban village residents. Drawing conclusions from the activities of devotion to communities: the ability of mothers about business online and the role of fintech 27point increased after the devotion to communities.